AB0699 Beta-Blockers Control Frequent Ventricular Ectopic Beats in Systemic Sclerosis: A Monocentric Study. (9th June 2015) - De Luca, G.; Bosello, S.; Parisi, F.; Berardi, G.; Rucco, M.; Canestrari, G.; Ficara, A.; Gabrielli, F.; Loperfido, F.; Ferraccioli, G.
Abstract : Background: Ventricular ectopic beats (VEBs) are associated with a substantial increase in the risk of sudden and total cardiac death, both in the general population and in Systemic Sclerosis (SSc) patients (1, 2). Beta-blockers are the mainstay of medical suppression of VEBs but are not routinely used in SSc patients due to possible Raynaud's phenomenon exacerbation and digital ischemic complications. Objectives: To evaluate safety and effectiveness of beta-blockers in SSc patients with heart involvement and arrhythmic burden. Methods: 96 patients of our cohort with signs and/or symptoms suggestive of cardiac involvement (dyspnoea, palpitations and/or rise of cardiac enzymes) underwent 24h-ECG-Holter. Among these, 14 patients with palpitations and/or frequent VEBs were treated with beta-blockers and prospectively followed. Ten patients were treated with bisoprolol (doses between 1.25-5 mg/day) and 4 with carvedilol. A complete assessment of disease characteristics and cardiac involvement was also performed and, after a mean follow-up of 14.0±9.4 months, a second 24h-ECG-Holter was performed. The effects on active ulcers were examined. Results: Eighteen patients (18.9%) presented VEBs >1000/24h at baseline. Considering the 14 patients treated with beta-blockers (mean age:47.5 years; mean disease duration:6.4 years; diffuse disease:57.1%; anti-Scl70 positivity: 64.3%), all of them presented an increase of troponin T and 8 (57.1%) a right bundle branch block. An history of digital ulcers was present in the majority of patients (71.4%) and 7 of them (50%) presented active ulcers at the time of study enrolment, 3 of whom with tissue loss. All patients were on sinus rhythm and none of them presented ST/T alterations; the mean number of VEBs at baseline was strikingly higher (6917.4±9911.9/24h) and 9 patients (64.3%) had a number of VEBs>1000/24h, that were polymorphic in 6 (42.8%). In 6 patients (42.8%), moreover, an episode of non-sustained ventricular tachycardia (NS-VT), the longest of 34 beats, was recorded. After beta-blockers treatment, the number of VEBs decreased in 10 patients (71.4%). The relative mean reduction was 74.7% (range:41.7-100%), while the absolute mean reduction was 4753.4±5610 VEBs/24h, with a range of 183-14408 VEBs/24h. The number of VEBs remained stable in the only 3 patients who presented a baseline number of VEBs<30/24h, and it increased in one patient. Considering the 9 patients with VEBs>1000/24h at baseline, in 3 (33.3%) the treatment with bisoprol led the number of VEBs far below this prognostic cut-off value, while among the 6 patients with baseline NS-VT, 3 had no more episodes recorded at follow-up. Despite continuative beta-blocker therapy, none of the patients presented a worsening of digital and legs ulcers, that rather improved in 4 patients, and none developed new digital ulcers. The Raynaud's phenomenon remained stable in all patients. Conclusions: Despite the small number of patients in this pilot study, our data suggest the efficacy of beta-blockers in reducing VEBs without an increase of digital ulcers complication or worsensing of Raynaud's phenomenon. References: Kostis JB. Am J Med 1988;84:1007-14. Ataklte F. Am J Cardiol 2013;112:1263-70. Disclosure of Interest: None declared